Nanopreparations Impact on Soybeans Growth and Development under Conditions of Piedmont Zone of East Kazakhstan - Marzhan Y. Rakhymberdina (AIDIC Servizi S.r.l., 2021)
The article provides the outcomes of field experiments related to studying influence of plant growth stimulant “Fullerenol” (foliar application) when soybeans are cultivated under conditions of piedmont zone of East Kazakhstan on agricultural lands. The obtained results of soybeans foliar application by fullerene derivatives ?60 enabled to identify the range of its concentration that have positive effect on biometric characteristics of soybeans herbage growth and indicate the need for further researches for improvement of concentrates compositions in order to strengthen growth stimulating functions. It has been observed that leaves, stems, and roots herbage are increased on 27-30 %, and when Fullerenol concentration 0.002 g/dm3 was used (from the entire range of concentrations), soybeans crop yield is increased by 8.51 %.